The Influence of Personality Competence and Discipline on the Performance of the Teachers - Huiser Mangalindung, Giovani; Sastrodiharjo, Istianingsih (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study is to investigate the influence of personality competence and discipline on the performance of the teachers. The problem studied is the teacher performance. This studies examines the effect of personality competence and discipline on the performance teachers. The methods used are qualitative and based on literature and library reseacrh approaches. Theoretical and historical analyses are used to understand personality competence and discipline. The implication of this study provide results that principals as teacher must be able to provide examples of discipline to students accompanied by communication that can lead to compliance. The principal includes his student for personality training to improve knowledge, skills, and attitudes to be able to carry out task and positions based on the personality needed by a student.